A critical appraisal of the process of regulatory implementation of novel in vivo and in vitro methods for chemical hazard and risk assessment. (November 2014) - Piersma, Aldert H.; Ezendam, Janine; Luijten, Mirjam; Muller, J.J. Andre; Rorije, Emiel; van der Ven, Leo T.M.; van Benthem, Jan
Abstract Regulatory toxicology urgently needs applicable alternative test systems that reduce animal use, testing time, and cost. European regulation on cosmetic ingredients has already banned animal experimentation for hazard identification, and public awareness drives toward additional restrictions in other regulatory frameworks as well. In addition, scientific progress stimulates a more mechanistic approach of hazard identification. Nevertheless, the implementation of alternative methods is lagging far behind their development. In search for general bottlenecks for the implementation of alternative methods, this manuscript reviews the state of the art as to the development and implementation of 10 diverse test systems in various areas of toxicological hazard assessment. They vary widely in complexity and regulatory acceptance status. The assays are reviewed as to parameters assessed, biological system involved, standardization, interpretation of results, extrapolation to human hazard, position in testing strategies, and current regulatory acceptance status. Given the diversity of alternative methods in many aspects, no common bottlenecks could be identified that hamper implementation of individual alternative assays in general. However, specific issues for the regulatory acceptance and application were identified for each assay. Acceptance of one-in-one replacement of complex in vivo tests by relatively simple in vitro assays is not feasible. Rather, innovative approaches using test batteries are required together with metabolic information and in vitro to in vivo dose extrapolation to convincingly provide the same level of information of current in vivo tests. A mechanistically based alternative approach using the Adverse Outcome Pathway concept could stimulate further (regulatory) acceptance of non-animal tests.